2019
DOI: 10.26442/00403660.2019.03.000043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the integral indices of the vectorcardiogram with the data of echocardiography in patients with idiopathic and chronic thromboembolic pulmonary hypertension

Abstract: The aim of the work is to compare vectorcardiographic (VCG) variables - spatial QRS-T angle and electrocardiographic ventricular gradient (VG) with echocardiography (EchoCG) data in patients with idiopathic pulmonary hypertension (IPH) and chronic thromboembolic pulmonary hypertension (CTEPH). Materials and methods. In 40 patients with IPH and 40 patients with CTEPH at the age of 45±12 years, systolic pulmonary artery pressure (SPAP); the sizes of heart chambers, parameters of RV systolic and diastolic functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recent medical research has demonstrated high efficiency and predictive value of integral VCG parameters [13], [14]. Also noteworthy are the works [15], [16], where, along with the components of the VG vector and the angle between its constituents, the decartogram of the repolarization acceleration is successfully used for diagnostic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent medical research has demonstrated high efficiency and predictive value of integral VCG parameters [13], [14]. Also noteworthy are the works [15], [16], where, along with the components of the VG vector and the angle between its constituents, the decartogram of the repolarization acceleration is successfully used for diagnostic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with IPH and CTEPH, [ 15 ] the change of QRS-T Angle is strongly correlated with SPAP, RV size, RA size, and RV systolic and diastolic function. An analysis has shown that QRS-T Angle can be combined with changes in echocardiography [ 15 ] for the definitive diagnosis of IPH and CTEPH patients.…”
Section: Introductionmentioning
confidence: 99%